Microarray analysis reveals the inhibition of nuclear factor-kappa B signaling by aristolochic acid in normal human kidney (HK-2) cells - Chen Ya-yin; Chiang Su-yin; Wu Hsiu-ching; Kao Shung-te; Hsiang Chien-yun; Ho Tin-yun; Lin Jaung-geng (Acta Pharmacologica Sinica, 2016)
Aim: To study the molecular mechanism underlying the effect of aristolochic acid (AA), a major active component of plants from the Aristolochiaceae family using microarray analysis. Methods: Human kidney (HK-2) cells were treated with AA (0, 10, 30, and 90 μmol/L) for 24 h, and the cell viability was measured by a 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide assay. Complementary DNA microarrays were used to investigate the gene expression pattern of HK-2 cells exposed to AA in triplicate. A quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) assay was used to verify the microarray data for selected nuclear factor kappa B (NF-κB)-regulated genes. Furthermore, the subcellular localization of NF-κB p65 was visualized by immunofluorescence confocal microscopy in HK-2 cells. The NF-κB activity was examined by a luciferase reporter assay in HK-2/NF-κB transgenic cells. Results: AA exhibited a dose-dependent cytotoxic effect in HK-2 cells and induced alterations in the gene expression profiles related to the DNA damage response, DNA repair, macromolecule metabolic process, carbohydrate metabolic process, DNA metabolic process, apoptosis, cell cycle, and transcription. In addition, 9 biological pathways associated with immunomodulatory functions were downregulated in AA-treated HK-2 cells. A network analysis revealed that NF-κB played a central role in the network topology. Among NF-κBregulated genes, 8 differentially expressed genes were verified by qRT-PCR. The inhibition of NF-κB activity by AA was further confirmed by immunofluorescence confocal microscopy and by NF-κB luciferase reporter assay. Conclusion: Our data revealed that AA could suppress NF-κB activity in normal human cells, perhaps partially accounting for the reported anti-inflammatory effects of some plants from the genus Aristolochia.